'Milk Pride': Lactivist Online Constructions of Positive Breastfeeding Value. Issue 1 (1st August 2018) - Mecinska, Lula
Based on six years of participant observation in lactivist spaces, this article traces one of the pathways from knowledge sharing to activism and mobilisation in breastfeeding support spaces online, and considers the ways in which lactivist spaces employ biomedical information and various images to create a sense of 'milk pride'. I want to argue that, although problematic, this is an important aspect of reclaiming biomedical evidence for women's benefit. By looking at images grouped thematically as 'wondrous milk', 'superpower', and 'liquid gold', the article demonstrates how the appropriation of biomedical discourses occurs at the grassroots level of the breastfeeding movement, understood here as the loosely connected networks of support present in online environments. It then moves to consider how these discourses are deployed to empower women to feel entitled to access specific rights and to extend these to the sphere of work within the household, typically invisible to the wage-work oriented economic sphere.